A machine oil cooler leakage detection method - CHEN LEI; SHI SHENGXIANG; ZHU WEI; PING ZHIQIAN; ZHANG JUNXIONG (2015)
The invention relates to a machine oil cooler leakage detection method characterized in that the method comprises steps of interface plugging and detection equipment connecting; leakage detecting and result determining; and result determining and processing. The leakage detecting and result determining step comprises two sub-steps of leakage rate detecting and leakage point detecting. According to the invention, a measuring principle of a pressure reducing method is employed; pressure drop in a workpiece is measured through a sensor and is converted into a leakage rate; local leakage detecting is carried out through a soap bubble method; the method is applicable to leakage detecting of machine oil coolers; part soaking is not needed in a leakage testing process; a normal working state of a machine oil cooler on an engine can be simulated; the operation is simple and convenient; the leakage detecting positioning is accurate; the measuring process is short in beat; measuring data can be bound with the engine and is traceable; and the machine oil cooler leakage detection method is applicable to automatic jug line production.